2018
DOI: 10.1111/maps.13226
|View full text |Cite
|
Sign up to set email alerts
|

Transitional impact craters on the Moon: Insight into the effect of target lithology on the impact cratering process

Abstract: We studied a data set of 28 well‐preserved lunar craters in the transitional (simple‐to‐complex) regime with the aim of investigating the underlying cause(s) for morphological differences of these craters in mare versus highland terrains. These transitional craters range from 15 to 42 km in diameter, demonstrating that the transition from simple to complex craters is not abrupt and occurs over a broad diameter range. We examined and measured the following crater attributes: depth (d), diameter (D), floor diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 83 publications
(202 reference statements)
2
25
0
Order By: Relevance
“…From the group of 244 craters, Chandnani et al () identified 117 simple craters based on uniform wall slopes and roughly bowl‐shaped cavities and observed that they are confined to flat or gradually sloping surfaces of the highlands and complex craters (the ones with central uplift) are more abundant in the mare. The study suggested that formation of simple craters is favored by a substrate whose attributes (strength, lithology, and topography) are spatially and vertically homogeneous (weaker but nonlayered highlands), whereas heterogeneity in terrain properties (layering in mare) facilitates cavity collapse, hence formation of shallower, complex craters (also previously reported by Cintala et al, , Cooper, , Dence, , Osinski et al, , Pike, , Quaide & Oberbeck, , Roddy, , Senft & Stewart, , Smith & Hartnell, , and Stewart & Valiant, ). Simple craters have been observed, experimented, and modeled to form with a d/D of ~0.2 on targets that have bulk properties such that they can be considered cohesionless, largely homogeneous, and not unusually porous (Kenkmann et al, ; Melosh, ; Melosh & Ivanov, ; Pike, , , ; Salamunićcar et al, ; Wood & Anderson, ).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…From the group of 244 craters, Chandnani et al () identified 117 simple craters based on uniform wall slopes and roughly bowl‐shaped cavities and observed that they are confined to flat or gradually sloping surfaces of the highlands and complex craters (the ones with central uplift) are more abundant in the mare. The study suggested that formation of simple craters is favored by a substrate whose attributes (strength, lithology, and topography) are spatially and vertically homogeneous (weaker but nonlayered highlands), whereas heterogeneity in terrain properties (layering in mare) facilitates cavity collapse, hence formation of shallower, complex craters (also previously reported by Cintala et al, , Cooper, , Dence, , Osinski et al, , Pike, , Quaide & Oberbeck, , Roddy, , Senft & Stewart, , Smith & Hartnell, , and Stewart & Valiant, ). Simple craters have been observed, experimented, and modeled to form with a d/D of ~0.2 on targets that have bulk properties such that they can be considered cohesionless, largely homogeneous, and not unusually porous (Kenkmann et al, ; Melosh, ; Melosh & Ivanov, ; Pike, , , ; Salamunićcar et al, ; Wood & Anderson, ).…”
Section: Introductionsupporting
confidence: 56%
“…The mare terrain is more coherent and stronger than the more porous regolith‐dominated highlands (Kiefer et al, ; Soderblom et al, ; Wieczorek et al, ) and therefore is expected to be more resistant to cavity collapse thereby supporting deeper craters. The mare themselves, which are composed of laterally extensive layers of basalt flows, likely interleaved with regolith layers (Head, ; Hiesinger et al, ; Philpotts & Schnetzler, ; Shoemaker & Hackman, ; Smith et al, ; Taylor, ), and this layering produces strength heterogeneities with depth that results in slumping/terracing in this diameter range (Chandnani et al, ; Cooper, ; Kalynn et al, ; Osinski et al, ; Pike, ; Quaide & Oberbeck, ; Roddy, ; Smith & Hartnell, ). So, the second hypothesis may not work for the mare.…”
Section: Introductionmentioning
confidence: 99%
“…This massive crust has been battered by impacts ever since its formation and is weaker owing to fracturing of rocks by shock waves and accumulation of impact ejecta and regolith over time. Though the highland material is less coherent than the younger mare, the homogeneity in its strength relative to the layered mare seems to be the primary factor in stabilizing the transient cavity, resulting in simple craters at larger diameters than in the mare (Krüger et al, ; Osinski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…At the position of the localized slumped material, their profiles show a gradual decrease in wall slopes to values that cover a wide range and can also be as low as~5°F ( Figures 7a-7d). Such a morphology qualifies for the definition of a transitional crater (Cintala et al, 1977;Cintala & Grieve, 1998;Howard, 1974;Kalynn et al, 2013;Osinski et al, 2018;Pike, 1974Pike, , 1977bPike, , 1988Plescia, 2015b;Robbins & Hynek, 2012;Smith & Sanchez, 1973). The craters whose wall slopes exhibit a change due to accumulated material that was primarily contributed by ejecta of impact craters on or adjoining the rims would be classified as simple craters.…”
Section: Crater With Localized Slumpsmentioning
confidence: 99%
See 1 more Smart Citation